The dramatic necessities of the Obligatory Scene in the feature film (Al-Academy, 2023)
Drama is one of the means of transmitting human experiences, as it presents within it the life ideas and visions of the spectator, who is subject to their influence on him, robbed of the will in front of its charm and various display arts, which invade him with its dimensions and affect his references, and this art form is based on stories revolving around personalities involved in events that have grown As a result of the struggle of two conflicting opponents, or two opposing forces or emotions generated as a result of a voluntary conflict, as this dramatic conflict represents the most important elements of those events, as it is embodied in an inevitable scene that emerges from other scenes, and this scene is sometimes subject to the expectations of the viewer who focuses all his efforts waiting for the moment of collision, Which, in turn, represents an Obligatory and binding scene that must be reached, and for this the researcher found it necessary to shed light on this topic because of its importance, so the research problem was represented in the following question: (What are the dramatic necessities that require the presence of an Obligatory Scene in the structure of the cinematic film?) As for the theoretical framework, it included two topics: the first: Obligatory Scene: Concept and Operation, and the second: the visual and sound foundations of the Obligatory scene in the narrative film. While the research procedures, the descriptive-analytical approach was taken, and an intentional sample that meets the research objectives, which included the king speech 2010 movie. The study concluded a number of results and conclusions.